2022
DOI: 10.1155/2022/7478223
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Learning: A Visualized Bibliometric Analysis Based on Bibliometrix from 2002 to 2021

Abstract: With the significant increase of studies on cross-cultural learning (CCL) in the recent two decades, it is essential to conduct a systematic review of various literature and their development processes. This article is aimed at revealing research hotspots and emerging trends in CCL studies. This study adapted a visualized bibliometric approach to analyze research articles in the Cross-Cultural Learning-Internet of Things area. We extracted papers published in respected journals as the dataset. Based on bibliom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…''Bibliometrics,'' a term first coined by Pritchard (1969), refers to the quantitative analysis of literature widely used in academic research since the early 1900s (Diem & Wolter, 2013). Over the years, bibliometric analysis has become increasingly popular in the study of intercultural and cross-cultural domains (e.g., Wang & Zhang, 2022;Yari et al, 2020). Bibliometric studies, if performed well, can lay solid foundations for promoting a field of research in meaningful and proactive ways since they help and enable researchers to (i) obtain an overall picture, (ii) perceive knowledge or research gaps, (iii) acquire novel and creative ideas for further investigation, and (iv) identify their potential contributions to the field (Donthu et al, 2021).…”
Section: Bibliometric Analysismentioning
confidence: 99%
“…''Bibliometrics,'' a term first coined by Pritchard (1969), refers to the quantitative analysis of literature widely used in academic research since the early 1900s (Diem & Wolter, 2013). Over the years, bibliometric analysis has become increasingly popular in the study of intercultural and cross-cultural domains (e.g., Wang & Zhang, 2022;Yari et al, 2020). Bibliometric studies, if performed well, can lay solid foundations for promoting a field of research in meaningful and proactive ways since they help and enable researchers to (i) obtain an overall picture, (ii) perceive knowledge or research gaps, (iii) acquire novel and creative ideas for further investigation, and (iv) identify their potential contributions to the field (Donthu et al, 2021).…”
Section: Bibliometric Analysismentioning
confidence: 99%
“…A total of 316 articles were identified, yielding 4085 references from 161 sources. The average number of citations per article was 12.16, indicating that most articles received a low number of citations (Niknejad et al, 2021;Wang and Zhang, 2022). The study identified 1241 authors and 398 author keywords, with an average of 5.41 author collaborations per article (Co-Authors per Article).…”
Section: Main Informationmentioning
confidence: 99%
“…Word Cloud is a data visualization technique used to represent text data of the published articles' keywords, in which the size of each word indicates its frequency or importance (Javed Ali et al, 2022;Nasir et al, 2020;Wang and Zhang, 2022). The term "Author's keywords" commonly denotes the topical and contextual inclinations of researchers in a given study, whereas "keywords plus" expresses the terms, methods, and techniques used in a particular study (Patil, 2020;Zhang et al, 2016).…”
Section: Most Frequent Wordsmentioning
confidence: 99%
“…Similarly, Scopus data were used to perform a bibliometric analysis of insurance literacy using the R package in [ 14 ]. The web-based interface of the R package, Biblioshiny, was used to perform bibliometric analysis on cross-cultural learning in [ 15 ]. In the study, WoS was used as a source of information, and the publication period was limited to 2002–2021.…”
Section: Introductionmentioning
confidence: 99%